The Evolution of Russia's State Security Agencies: a Historical Analysis from the CHEKA to the FSB - Madatov, Oleg Yakovlevich (Genesis: исторические исследования, 2025)
The work is devoted to the analysis of the historical development of the state security agencies of Russia, from the moment of their creation in 1917 to the present. The relevance of the research is due to the high historical and institutional importance of security agencies for the Russian state, their influence on political processes, economic development and cultural life of the country. Of particular importance is the analysis of the adaptation of services to modern challenges and threats in the context of political instability and reorganizations.The purpose of the article is a comprehensive analysis of the evolution of Russia's state security agencies over the course of more than a hundred years of their existence, identifying patterns and continuity in their activities, and evaluating the effectiveness of services during critical periods of history. The subject of the research is the stages of formation, development and reform of the state security bodies of Russia, their structure, functions, working methods, role in ensuring national security and influence on political and socio-economic processes in the country.The research methodology consists of a historical and legal analysis of regulations, archival materials and scientific publications, a comparative analysis of various periods of development of security agencies, and the study of biographies of key figures involved in the development of the services. The novelty of the research is a comprehensive and multifaceted analysis of the evolution of Russian state security agencies over more than a hundred years of their existence, covering the periods: pre-war (1917–1941), war (1941–1945), post-war before the collapse of the USSR (1946–1991) and modern (from 1991 to the present). Special attention is paid to the analysis of the influence of political leaders, historical events and socio-economic factors on the formation and development of security agencies. The modern structure and functions of the Federal Security Service are the product of a long historical development reflecting the specifics of state building and the evolution of the national security system of the Russian Federation. Throughout history, the State security agencies, despite numerous reorganizations, have maintained their continuity and played an important role in ensuring the security of the country. The principles of the FSB's activities are based on the traditions laid down by its founders and leaders, including the unity of the system of bodies, centralization of management, legality and humanism. The flexibility and adaptability of the system is noted, as well as the high professionalism and dedication of the staff.